International expert consensus on micronutrient supplement use during the early life course - Irene Cetin; Roland Devlieger; Erika Isolauri; Rima Obeid; Francesca Parisi; Stefan Pilz; Lenie van Rossem; Maternal Nutrition Delphi Study Group; Régine Steegers-Theunissen (BMC Pregnancy and Childbirth)
Abstract Background Growing evidence demonstrates that maternal nutrition is crucial for the health of the mother-to-be, and early life course of the offspring. However, for most micronutrients, guidelines are inconsistent. This Delphi study aimed to investigate the level of expert consensus on maternal nutrition and micronutrient needs during preconception, pregnancy and lactation. Methods We conducted a two-round web-based Delphi survey on various topics including general approaches to diet and supplement use, and existing guidelines. For the periods of preconception, pregnancy and lactation, questions focused on the importance and strength of evidence for supplement use with the following micronutrients for low- and high-risk populations: folic acid, choline, iodine, magnesium, calcium, iron, selenium, docosahexaenoic acid (DHA), and vitamins B1, B2, B6, B12, D and K. Results Thirty-five experts participated in the panel, who were healthcare professionals (HCPs), researchers and joint HCP-researchers with expertise in nutrition, gynaecology and/or obstetrics. Panellists reached consensus on the importance of diet and dietary supplement use during pregnancy and agreed on the lack of clarity and consistency in current guidelines, and the need for education in these areas for HCPs, pregnant people and the general population. For general low-risk populations, there was consensus on the importance of supplement use with iron and vitamin D from preconception through lactation, with folic acid and iodine from preconception through the second and third trimesters, respectively, with DHA from the first trimester through lactation and with calcium during lactation. Panellists agreed that the evidence for supplement use with each of these micronutrients during these phases to improve outcomes and/or foetal development is strong, except for vitamin D (preconception), DHA (first trimester), and iron (both periods). There was also consensus that supplement use advice should be tailored for people following vegan/vegetarian diets, restricted diets due to food intolerances, obesity, polycystic ovary syndrome, diabetes mellitus, and previous nutrition-related pregnancy complications. Conclusion The findings revealed robust consensus on various aspects of maternal nutrition, including the need for education, the lack of consistency in current guidelines on supplement use, the importance of supplement use across specific phases of pregnancy and the at-risk groups requiring tailored approaches.